Maximization of the Olfactory Receptor Neuron Selectivity in the Sub-Threshold Regime - Vidybida, A.K. (Ukrainian Journal of Physics, 2023)
It is known that if odors are presented to an olfactory receptor neuron (ORN) in a sub-threshold concentration – i.e., when the average value of the number of the ORN bound receptor proteins (RPs) is insufficient for the generation of spikes, but such a generation is still possible due to fluctuations around the average value – the ORN selectivity can be higher than the selectivity at higher concentrations and, in particular, higher than the selectivity of the ORN’s RPs. In this work, the optimal odorant concentration providing the highest ORN selectivity is found in the framework of a simplified ORN model, and the dependence of the highest selectivity on the total number of RPs in the ORN, N, and its threshold value N0 is derived. The effect of enhanced selectivity in the sub-threshold regime is best manifested, if N0 is close to either unity or N. It is also more pronounced at large N-values.